2008
DOI: 10.1590/s0004-282x2008000200020
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the neurons from the myenteric plexus in the ileum of rats submitted to severe protein deficiency

Abstract: -The effects of protein malnutrition on the quantitative aspects of the myenteric plexus in the ileum of adult Rattus norvegicus were assessed. Thirty 90-day-old rats were divided into two groups: Control Group (CG, n=15) and Experimental Group (EG, n=15). The CG received 26% protein chow and the EG received 4% protein chow for 90 days. At the end of the experiment, the animals from the CG weighed 369.63±26.33, and the ones from the EG 215.34±56.31. The ileum was submitted to Giemsa, NADH-and NADPH-diaphorase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
2
9
0
3
Order By: Relevance
“…Through NADPH-diaphorase, we noticed an increase of the neurons expressing the nitric oxide synthase (NOS) (around 2.20%) for the animals fed with a lack-of-protein diet. Similar result was noticed on the ileum where a 9.2% increase of positive NADPH-d neurons occurred for the animals receiving 4% protein (Moreira et al 2008), demonstrating that these neurons are less vulnerable to cell death (Cowen et al 2000). However, a study with 8% protein demonstrated the occurrence of no alteration on the neuronal density of rat duodenum through NADPH-d histochemistry (Mello et al 2004).…”
Section: Myenteric Neurons In Malnourished Ratssupporting
confidence: 67%
See 2 more Smart Citations
“…Through NADPH-diaphorase, we noticed an increase of the neurons expressing the nitric oxide synthase (NOS) (around 2.20%) for the animals fed with a lack-of-protein diet. Similar result was noticed on the ileum where a 9.2% increase of positive NADPH-d neurons occurred for the animals receiving 4% protein (Moreira et al 2008), demonstrating that these neurons are less vulnerable to cell death (Cowen et al 2000). However, a study with 8% protein demonstrated the occurrence of no alteration on the neuronal density of rat duodenum through NADPH-d histochemistry (Mello et al 2004).…”
Section: Myenteric Neurons In Malnourished Ratssupporting
confidence: 67%
“…When we compared our findings with those from other intestinal segments from the same experimental animals, we verified that there is no alteration with respect to the total population for both large and small intestines, but increase of the positive-NADPH-d myenteric neurons in the small intestine (Moreira et al 2008) as well as their decrease in the large intestine , what demonstrated that large intestine suffer more injuries resulting in diarrhea for the decrease of nitrergic neurons and increase of cholinergic neurons responsible for intestinal contraction.…”
Section: Myenteric Neurons In Malnourished Ratssupporting
confidence: 56%
See 1 more Smart Citation
“…Regarding the external muscle, we verified that it underwent virtually no morphological changes due to the food restriction imposed on the DRG. This is indicative that these rats were probably not protein-energy malnourished, since atrophy of intestinal smooth muscle is common in these cases, as a compensatory mechanism due to lower intake of amino acids in the diet (De Azevedo et al, 2007;Moreira et al, 2008;Hermes et al, 2008;Franco et al, 2010;Sant'Ana et al, 2012;De Lima et al, 2012).…”
Section: Duodenummentioning
confidence: 99%
“…Alterações nos neurônios do plexo mioentérico são responsabilizadas por manifestações como anorexia, constipação, diarreia, perda de peso, vômitos, náusea, entre outras evidenciadas em diferentes condições experimentais como diabetes, (ZANONI et al, 2005;ALVES et al, 2006;CHANDRASEKHARAN;SRINIVASAN, 2007;SHOTTON;ADAMS;LINCOLN, 2007;PEREIRA et al, 2008;SILVERIO et al, 2009);envelhecimento (SANTER, 1994;JOHNSON et al, 1998;BRITTO MARI et al, 2008;GAGLIARDO et al, 2008); desnutrição (MOREIRA et al, 2008); desnutrição ao longo do envelhecimento (COWEN et al, 2000;SCHOFFEN et al, 2005;ARAÚJO et al, 2006); infecções (SUGAUARA et al, 2008(SUGAUARA et al, , 2009; enterites e colites (BOYER et al 2005(BOYER et al , 2007LOMAX et al, 2006) e carên-cia protéica (ALVES et al, 2009), intoxicações (PEREIRA;STABILLE, 2006;CORREA et al, 2011;PEREIRA et al, 2013).…”
Section: Introductionunclassified